SOCIAL ASSISTANCE IN ROMANIA IN THE CONTEXT OF EUROPEAN INTEGRATION AND GLOBALIZATION - Gheorghe MATEI; Nicolae TUDOSE (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2015)
Given the changes that have occurred within the demographic structure of the population and the framework of the labour market, there is a both a global and national concern towards the continuous reconceptualization of the field of assistance. Although during the last decades our country's political and economic maps have innately influenced social practices, the social assistance system in Romania is still in transition. The aim of the present study is to progressively undertake a critical review of the circumstances that have led to the development of the national social assistance system so that the specific advantages and disadvantages of current practices and characteristics be identified. Such aspects are to serve as basis for the opposite forecast of the opportunities and challenges that the Romanian social assistance system is to face, with a direct and subsequent impact upon the choice of tools for an optimal social intervention that is to generate social welfare. Thus, while Romania's concern for social issues has seen no intermission, as it continuously sought the satisfaction of the more and more diverse social needs and expectations, its accession to the European Union and the later requirements imposed by the need to align to the standards imposed by European superstructures have lead the way to new accumulations in terms of social policy, with a resolute impact upon its major objectives and expected aims. In this context, the transition from passive to active social practices seeks to ensure the overall transformation of the system, a basis for a sound investment in human capital.